Perioperative Intravenous Lidocaine Infusion for Postoperative Analgesia in Patients Undergoing Surgery of the Spine: Systematic Review and Meta-Analysis. Issue 1 (1st July 2021) - Licina, Ana; Silvers, Andrew
Abstract: Objective: We conducted a systematic review and meta-analysis to examine the impact of perioperative intravenous lidocaine infusion on pain management scores, opioid consumption, adverse events, and hospital length of stay in patients undergoing spinal surgery. Methods: We included randomized controlled trials evaluating the use of perioperative intravenous lidocaine in adult and pediatric patients undergoing spinal surgery. Primary outcomes were postoperative pain scores at rest and at 2, 4–6, 24, and 48 hours and adverse events attributable to lidocaine administration. We searched electronic databases from their inception to the present. We used Cochrane's standard methods. We used a random-effects model to synthetize data. We conducted three subgroup analyses: patients undergoing major surgery vs patients undergoing minor surgery, patients with chronic pain conditions vs patients without, and adult vs pediatric patients. Results: A total of eight studies were included that compared patients having intravenous lidocaine (n = 349) with controls (n = 343). Intravenous lidocaine administration was associated with significantly reduced visual analog pain scores at 2 hours (mean difference [MD] = −1.13), 4–6 hours (MD = −0.79), and 24 hours (MD = −0.50) postoperatively. In the adults, efficacy of treatment was extended to 48 hours (MD = −0.72). Perioperative intravenous lidocaine administration was associated with reduced perioperative opioid consumption at 24 and 48 hours, as well as decreased hospital length of stay. Conclusion: Perioperative intravenous lidocaine infusion consistently improves analgesic measures in adult and pediatric populations in the first 24 hours, with an effective decrease in opioid consumption noted to 48 hours. These results are most generalizable in the adult population in the first 4–6 to 24 postoperative hours.